Impact of credit risk on momentum and contrarian strategies: Evidence from South Asian markets - Ahmed Imran Hunjra; Tahar Tayachi; Rashid Mehmood; Sidra Malik; Zoya Malik (Risks, 2020)
We examine the profitability of the momentum and contrarian strategies in three South Asian markets, i.e., Bangladesh, India, and Pakistan. We also analyze, whether credit risk influences momentum and contrarian return for these markets from 2008 to 2014. We use default risk that relates to non-payments of debts by firms as a measure of credit risk. For that purpose, we use distance to default (DD) by Kealhofer, McQuown, and Vasicek (KMV) model as a proxy of credit risk. We calculate the credit risk and form the momentum and contrarian strategies of the firms based on high, medium, and low risk. We find that in all three markets, the momentum and contrarian returns are significant for medium and high credit risk portfolios and no momentum and contrarian returns for low credit risk portfolios.
Keywords: 330; contrarian returns; credit risk; KMV model; momentum returns; stock market